Torn Apart and Coexisting: The Contradictory Logic of Racial Predicament in “The Displaced Person” - Liu, Shan (International Journal of Language and Literary Studies, 2026)
Taking Flannery O’Connor’s short story “The Displaced Person” as its object of study, this paper employs Marxist contradictory analysis to conduct an in-depth examination of the structural tensions that intensified in the American South after World War II. These tensions emerge most clearly in the conflicted relationship between foreign immigrants and the local white community. By analyzing the transformation of principal and secondary contradictions, the law of the unity of opposites, and the inevitability of violence under the universality of contradiction, this study demonstrates how Mrs. McIntyre’s position shifts from economic rationality to the defense of racial order. It further reveals how characters such as the Shortleys construct the legitimacy of their own identities through the exclusion of “the Other,” and how violence ultimately becomes the most extreme expression of irreconcilable social contradictions.